2023
DOI: 10.1515/zpch-2023-0243
|View full text |Cite
|
Sign up to set email alerts
|

Cd/SBA-15 heterogeneous catalyst used for acetic acid conversion: pseudo-homogeneous kinetic model, response surface methodology, and historical data design

Veli Şimşek

Abstract: Mesoporous materials (MMs) in the Santa Barbara Amorphous (SBA) family can be used as catalysts or support materials (SMs) for catalysts because they have controllable pore structure, thermal and chemical stability, and their surface properties can be modified easily depending on the desired reaction type. Surfactant (Pluronic p123; it is a symmetric triblock copolymer comprising poly and its chemical formula; HO(CH2CH2O)20(CH2CH(CH3)O)70(CH2CH2O)20H), a silica source (such as Tetraethyl orthosilicate: TEOS; S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Figure2shows the results of the low and high-angle XRD analysis of the SBA-15 and the hybrid samples consisting of different loadings of TiO 2 , Fe, and Cd on SBA-15. Similar results are shown in our previous work dealing with the activities of Cd/SBA-15 for the esterification of acetic acid with methanol[27,28]. According to the results of the XRD analysis of the SBA-15, four main Bragg peaks were obtained (Figure2a), corresponding to the d(100), d(110), d(200)[29,30], d(210)[31], and d(300)[32] characteristic peaks.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…Figure2shows the results of the low and high-angle XRD analysis of the SBA-15 and the hybrid samples consisting of different loadings of TiO 2 , Fe, and Cd on SBA-15. Similar results are shown in our previous work dealing with the activities of Cd/SBA-15 for the esterification of acetic acid with methanol[27,28]. According to the results of the XRD analysis of the SBA-15, four main Bragg peaks were obtained (Figure2a), corresponding to the d(100), d(110), d(200)[29,30], d(210)[31], and d(300)[32] characteristic peaks.…”
supporting
confidence: 87%
“…The FT-IR analysis of SBA-15 showed that the peaks between wavelengths of 445 cm −1 and 1046 cm −1 belonged to the characteristic structure of SBA-15 (Figure 3) [27,28]. Symmetrical and asymmetrical structures of tensile and flexible vibrations of Si-O and SiO 2 were observed at 938, 789, and 1044 cm −1 [37,38].…”
Section: Ft-ir Analysismentioning
confidence: 96%
See 1 more Smart Citation